Relationships between feedlot health, average daily gain, and carcass traits of Angus steers - Hands, M.L.; Marston, T.T.; Corah, L.R.; Reinhardt, Christopher D.; Waggoner, Justin W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Morbidity reduces performance and quality grade, but the effects of morbidity on quality grade independent of its effect on carcass fatness are rarely documented. As feedlot cattle fatten, a greater proportion of their daily carcass gain goes to fat deposition, and greater carcass fat is consistent with greater marbling score. Higher-grading cattle are often assumed to have reduced feedlot performance. Objectives of this research were to document the impacts of various animal and non-animal factors on feedlot average daily gain, health, and carcass traits in Angus steers and to correlate quality and yield grade components of carcass with live performance.
Keywords: Beef; Feedlot; Daily gain; Carcass traits; Angus steers